(3GdMeGjI GdLfGFjI dhSGFd Gdfbd GdLhi h GdHMQi (B: s (3OQGSI ebGQfI (B/ s - (3MeOi MSf eMeO GdfgQis; (3YeQ eMeO eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3gOa GdHMK Edi Gdhbha Ydi eOi GdMeGjI GdLfGFjI dhSGFd Gdfbd GdLhi h GdHMQi ai HYV GdGJaGbjGJ GdOhdjI(B: (3h GdJTQjYGJ GdebGQfI (B((3GdGfLdjRjI(B-(3GdaQfSjI(B-(3GdeUQjI(B): (3eY EdbGA GdVhA Ydi OhQ GdTQWI ai gPG GdeLGd(B. (3h bO JJfhY GdLQGFe GdeQJcHI Ch GdehLgI VO hSGFd Gdfbd GdLhi h GdHMQi ef JNQjH h EJdGa ddWGFQI ai GdeWGQ Ch GdSajfI ai GdejfGA(B: (3h bO JJYQV GdWGFQI dJZjjQ eSGQgG ai GdLh HGdbhg(B: (3ceG bO JJYQV GdSajfI dLQjeI GdbQUfI h gi ai YQV GdHMQ(B: (3eeG cGf dRGeG Ydi GdOhd Cf JSGQY Edi YbO GdGJaGbjGJ GdKfGFjI(B: (3GdEbdjejI Ch GdOhdjI(B: (3eY hVY GdYbhHGJ GdefGSHI dJdc GdLQGFe GdNWjQI ai JTQjYGJgG GdhWfjI GdOGNdjI(B. (3CXgQJ GdOQGSI GdChLg GdGjLGHjI ai GdGJaGbjGJ GdOhdjI GdMeGFjI h GdJTQjYGJ GdebGQfI ai Pdc GdeLGd(B: (3h gPg ChLg GdJi TGHJgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2014s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B675-703s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdMeGjI GdLfGFjIs; (3Gdfbd GdLhis; (3hSGFd Gdfbds; (3Gdfbd GdHMQjs; (3NWa GdWGFQGJs; (3GdbQUfI GdHMQjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs